2019
DOI: 10.1016/j.jdeveco.2019.102379
|View full text |Cite
|
Sign up to set email alerts
|

Women's political participation and intrahousehold empowerment: Evidence from the Egyptian Arab Spring

Abstract: Egyptian women have played an unprecedented role in the Arab Spring democratic movement, possibly changing women's perception about their own rights and role. We question whether these events have translated into better outcomes within Egyptian households. We conjecture that potential changes must have been heterogeneous and depended on the local intensity of protests and women's participation over 2011-13. We exploit the geographical heterogeneity along these two margins to conduct a double difference analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 51 publications
4
24
3
Order By: Relevance
“…Our FLFP results are in opposition to the two studies on the Egyptian Arab Spring which find improvement in women's status indicated by improvements in relative FLFP (El-Mallakh et al, 2018) and women's intrahousehold decision-making power (Bargain et al, 2019).…”
Section: Arab Spring Exposure and Women's Outcomescontrasting
confidence: 99%
See 3 more Smart Citations
“…Our FLFP results are in opposition to the two studies on the Egyptian Arab Spring which find improvement in women's status indicated by improvements in relative FLFP (El-Mallakh et al, 2018) and women's intrahousehold decision-making power (Bargain et al, 2019).…”
Section: Arab Spring Exposure and Women's Outcomescontrasting
confidence: 99%
“…Our findings contradict those from EI-Mallakh (2018) and Bargain et al (2019) on the influences of Arab Spring protests on gender equality, suggesting that their findings from Egypt cannot be generalized to other MENA countries. On the other hand, our findings are consistent with those in Fox et al (2016), which shows that the support for "secular feminism" has declined across Arab Spring countries.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…I compare this conceptualization of shock-exposure to measures of treatment intensity used in past studies. The growing body of work that examines the effect of the Arab Spring protests uses different measures of protest intensity such as number of protesters (Acemoglu et al, 2018), number of martyrs (El-Mallakh et al, 2018) and number of fatalities, injuries and arrests (Bargain et al, 2019). I do not use such measures in this study for three key reasons.…”
Section: Religionmentioning
confidence: 99%